Perlindungan Wanita dan Kesetaraan Gender dalam Konteks Hak Asasi Manusia - Wanda, Anika Sukma (Universitas Islam Indragiri, 2023)
Law Number 23 of 2004 concerning the Elimination of Domestic Violence is an important component of the current legal system. This paper aims to study various types of violence against women, including violence that occurs at home, at work, on campus, and in society as a manifestation of the imbalance in the relationship between women and men. Additionally, it will look at the issue of gender equality from a human rights perspective in Indonesia. The author's aim is to identify various types of violence against women in Indonesia. This includes physical, sexual, economic, political, and psychological violence, as well as violence that can be perpetrated by individuals, groups, or even state entities. The author uses qualitative research methods and a normative juridical approach. According to the literature review, women are a vulnerable group and women's rights are an important component of human rights. In Indonesia, international laws and treaties protect women's rights and promote gender equality. However, law enforcement in Indonesia is not adequate to protect women and realize gender equality because women are seen as weak creatures, as well as a lack of knowledge and understanding of women's rights.